Minerales en la Nutrición Animal en la América Latina - Alba, Jorge de; Davis, George K. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
An attempt is made to correlate the world literature on mineral nutrition in farm animals, with existing data from Latin America. The most comprebensive map of deficient aveas can be made in the case of lodine, utilizing some of the data from buman goiter belts.